DIABETIC GANGRENE OF THE LOWER LIMBS – ANALYSIS OF TREATMENT OUTCOMES AND LONG-TERM SURVIVAL - A.R. Bababekov; U.K. Kasimov (Western European Studies, 2025)
Diabetic ulcers are not only a common problem but also one of the serious and costly complications of diabetes. Significant risk factors for amputation in patients include male sex, a history of nicotine use, duration of foot ulcers, the presence of destructive changes in the foot, and excessive body weight. A history of ulcers increases the risk of developing another ulcer in diabetic patients. In 20–58% of patients, a new ulcer develops within one year after wound healing. Studies have shown that in patients with recurrent foot ulcers, the rate of amputations is ultimately 2.23 times higher than in patients with primary foot ulcers [7,8,12]. Objective. To study long-term survival and treatment outcomes in patients with diabetic gangrene of the lower limbs (DGL) after limb amputation at various levels
Keywords: neuro-ischemic form of diabetic foot syndrome; diabetic ulcer; diabetes mellitus